2002
DOI: 10.1191/0269215502cr518oa
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge and home rehabilitation after hip fracture achieves functional improvements: a randomized controlled trial

Abstract: This trial further supports the practice of accelerated discharge from hospital and home-based rehabilitation in selected patients recovering from hip fracture. Such a practice appears to improve physical independence and confidence in avoiding subsequent falls which may have implications for longevity and overall quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
173
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(181 citation statements)
references
References 16 publications
6
173
1
1
Order By: Relevance
“…Ten previously published multi-component home-based rehabilitation studies after a hip fracture, which investigated the effects of rehabilitation on mobility recovery compared to usual care, were found (Crotty et al 2002, Crotty et al 2003, Latham et al 2014, Shyu et al 2010, Tseng, Shyu & Liang 2012, Tinetti et al 1999, Ziden, Frandin & Kreuter 2008, Ziden, Kreuter & Frandin 2010. The studies include seven different trials, and from those, three trials included two separate papers.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
See 2 more Smart Citations
“…Ten previously published multi-component home-based rehabilitation studies after a hip fracture, which investigated the effects of rehabilitation on mobility recovery compared to usual care, were found (Crotty et al 2002, Crotty et al 2003, Latham et al 2014, Shyu et al 2010, Tseng, Shyu & Liang 2012, Tinetti et al 1999, Ziden, Frandin & Kreuter 2008, Ziden, Kreuter & Frandin 2010. The studies include seven different trials, and from those, three trials included two separate papers.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
“…Some of the trials included longer follow-up periods after the intervention, but when the effects of the intervention were compared to those of usual care during the intervention period, four studies found better mobility results after the intervention. Latham et al (20014) reported better results in the Short Physical Performance Battery and functional balance, Orvig et al (2011) higher physical activity, Shyu et al (2010) increased quadriceps strength and walking ability, Tinetti et al (1999) better upper extremity strength, and Crotty et al (2002) less fear of falling for the intervention group than for the usual care group. Nevertheless a need for further studies of home-based rehabilitation programs among hip fracture patients is widely acknowledged (Handoll et al 2009, Handoll, Sherrington & Mak 2011, Ftouh et al 2011, Donohue et al 2013.…”
Section: Rehabilitation After Hip Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…Choong et al [8] reported that discussion of the treatment process and goals with the patient, the patient's family, and the medical staff led to shortening of the hospitalization period. In addition, early exercise with weight-bearing on the affected leg [9] and shortening of the hospitalization period [10] are effective approaches for functional recovery, as well as being of benefit financially.…”
Section: Introductionmentioning
confidence: 99%
“…A number of trials have favourably compared the outcomes of home-based rehabilitative therapy with care provided in either a hospital or other institutional setting. [37][38][39] Benefits of home-based rehabilitation have included improved physical independence, 38 confidence in avoiding subsequent falls, 38 lower caregiver burden at 12 months 38 and lower functional decline. 39 However, care of the patient is transferred onto either their family or members of the community, meaning that this option is only feasible if adequate social support networks are available.…”
Section: Rehabilitation Programmesmentioning
confidence: 99%